Rules and Routines in Covid-19: How Are The Applications In Physical Education Learning In School? - Panuwun Joko Nurcahyo; Rifqi Festiawan; Didik Rilastiyo Budi; Arfin Deri Listiandi; Ngadiman Ngadiman; Kusnandar Kusnandar; Muhamad Syafei (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2020)
This study aims to determine the application of the rules (rules) and routines (routines) in the learning process of Physical Education in SMP Negeri throughout the Banyumas Regency. This research is quantitative descriptive research. The research method used was a survey method. The subjects in this study were physical education teachers in Banyumas Regency, totaling 36 schools. The sampling technique uses a total sampling technique. The research instrument used in the form of a questionnaire application of rules (rules) with a validity coefficient of 0.925 and a reliability coefficient of 0.991, as well as a routine questionnaire (routines) with a validity coefficient of 0.925 and a reliability coefficient of 0.987. Data analysis techniques using quantitative descriptive analysis presented in the form of a percentage. The results showed that: (1) The application of the rules in Physical Education learning in state junior high schools in Banyumas Regency was in the category of